Engineering Innovations Vol. 14 - Afrooz Barnoush; Elena Gordo Odériz; José Luis Ordóñez-Ávila; Ian McAndrew; Rizki Agam Syahputra; Ambuj Sharma; Lee Zhi (Trans Tech Publications Ltd, 2025)
The 14th volume of the journal Engineering Innovations includes articles that accent the reader's attention on the latest advances and results of research in materials science, construction and architecture, renewable energy, development and applications of IoT systems, mechatronics and data and image processing. The presented articles will be helpful to many engineers and researchers in engineering sciences.